PREVALENSI DAN RISIKO MEROKOK TERHADAP PENYAKIT PARU DI POLIKLINIK PARU RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR - Sajinadiyasa, I G K; Bagiada, I M; Ngurah Rai, I B (journal of internal medicine; Vol. 11, No. 2 Mei 2010, 2012)
Cigarette smoking is the single largest preventable cause of premature death in the world today. Estimates of the number of yearly deaths from smoking-related causes exceed 400,000 (about one-sixth of all deaths). About 23% of the U.S. population in the year 2000 smoked, and another 22% used to smoke. United Kingdom reported 12.5 million of adult smokers in 2003 (about 26% of UK population). Indonesia also reported very high prevalence of cigarette smoking (about 50 ! 70%). While in Tenganan village, Bali, smoking prevalence reported about 26.3%. Smoking cessation is the key point in managing patients with tobacco related diseases, especially lung diseases. We conducted a cross sectional study to Þ nd out smoking prevalence and smoking contributions to lung diseases among patients in pulmonology outpatient clinic of Sanglah hospital, Bali. Among 108 patients, we found 77 patients (71.3%) exposed to cigarette smoking. Among these patients, we found 11 (10.2%) patients still smoking, 55 (50.9%) were ex-smokers, and 11 (10.2%) were passive smoker. Among active smokers and ex-smokers, we found 34 patients (31.5%) were light smoker, 25 (2.1%) were moderate smoker, and 7 (6.5%) were heavy smoker according to Brinkman index. The most frequent lung problem found in this study was lung TB (42.6%), while smoking exposure happens in 76.1% patients. As the conclusion, smoking prevalence is high among patients come to pulmonology outpatient clinic of Sanglah hospital.
Keywords: smoking, lung diseases, outpatient